Endurance performance in Paralympic sitting sports - Testing and training - Baumgart, J. K.; Skovereng, K.; Ettema, G.; Sandbakk, O. (NVC Conference 2017, 5.-6. October 2017, Are, Sweden, 2017)
In endurance sports, three factors mainly play a role for endurance performance: 1) maximal oxygen uptake (O2max), 2) the % of O2max used at the anaerobic threshold (ANT) and 3) efficiency[1]. In athletes with a disability, who exercise in an upper-body mode, O2max is rarely reached and peak oxygen uptake (O2peak) is used instead. This is in part due to the upper-body mode itself that activates a relatively low muscle mass and consequently does not fully tax the cardio-respiratory system. Furthermore, the impact of an individual`s disability on movement function and physiological capacity reduces O2peak. In our research, we found that as compared to a group of similarly upper-body trained able-bodied controls, O2peak values in a group of Paralympic sitting athletes who mostly had spinal cord injuries are lower due to their disability-related limitations (45 ± 6 vs 35 ± 7 mL/kg/min, respectively). This is likely related to blood pooling in the legs and the abdomen, autonomic dysfunction and a negative long-term effect of exercising with a limited muscle mass on cardiovascular function[2,3].